Optimizing the Traditional Melinjo Chip Production Process: A Case Study in Bulakwaru Village - Agus Susilo (Lembaga Pengembangan Kinerja Dosen, 2026)
The production of traditional melinjo chips in Bulakwaru Village, Tegal Regency, represents an important component of local wisdom–based economic activities and contributes to the livelihood of many small entrepreneurs in the area. However, despite its promising market potential, the production process still encounters several challenges that limit business growth and efficiency. These obstacles include dependence on weather conditions during the drying process, limited and traditional production equipment, fluctuations in the availability of melinjo raw materials, restricted access to business capital, and limited marketing strategies. This study aims to identify these key challenges and propose practical solutions to enhance the efficiency and sustainability of melinjo chip enterprises. The research uses a qualitative descriptive method, collecting data through observation, interviews, and documentation involving melinjo chip entrepreneurs in Bulakwaru Village. The findings suggest several potential strategies, including diversifying drying techniques, modernizing production equipment, establishing partnerships with melinjo farmers, improving human resource skills through training, strengthening business institutions, encouraging collaboration with government agencies, and utilizing digital marketing. These efforts are expected to increase competitiveness and improve the long-term welfare of local melinjo chip entrepreneurs.